2023
DOI: 10.1021/acsami.2c20464
|View full text |Cite
|
Sign up to set email alerts
|

Highly Aligned Cellulose/Polypyrrole Composite Nanofibers via Electrospinning and In Situ Polymerization for Anisotropic Flexible Strain Sensor

Abstract: Flexible strain sensors have recently attracted great attention due to their promising applications in human motion detection, healthcare monitoring, human–machine interfaces, and so forth. However, traditional uniaxial strain sensors can only detect strain in a single direction. Herein, an anisotropic flexible strain sensor is fabricated based on conductive and highly aligned cellulose composite nanofibers, via facile electrospinning cellulose acetate, deacetylation, and in situ polymerization of pyrrole, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 47 publications
0
17
1
Order By: Relevance
“…Tunneling effect is one the most common application mechanisms for motion of electrons, which occurred on crossing the interparticles distance. [3,9,[51][52][53] There is a potential energy barrier between adjacent but not connected conductive fillers. Based on quantum mechanics, it is possible for electrons to move through the barriers between adjacent conductive fillers, which is the tunneling effect.…”
Section: Electrospinning Fibrous Strain Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tunneling effect is one the most common application mechanisms for motion of electrons, which occurred on crossing the interparticles distance. [3,9,[51][52][53] There is a potential energy barrier between adjacent but not connected conductive fillers. Based on quantum mechanics, it is possible for electrons to move through the barriers between adjacent conductive fillers, which is the tunneling effect.…”
Section: Electrospinning Fibrous Strain Sensorsmentioning
confidence: 99%
“…Meanwhile, this PEDOT:PSS-PVA nanofiber sensor presents good sensitivity with GF of 396. Li et al [3] reported an anisotropic cellulose/polypyrrole (PPr) flexible strain sensor via electrospinning cellulose acetate, deacetylation, and in situ polymerization of pyrrole (Figure 4e). The strain sensor shows good mechanical properties because of strong hydrogen bonding between cellulose and PPr, and investigates the effect of perpendicular to and parallel to the nanofiber structure on the sensor performance with sensitivities of 0.73 and 0.01, respectively.…”
Section: Electrospun Sensor Of Conductive Spinning Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…This can solve the weak interface interaction between a rigid highly conductive filler and a flexible polymer matrix. Moreover, among many conductive polymers, polyaniline (PANI) and polypyrrole (PPy) are of low cost, easy to synthesize, stable in air, and with controlled physical properties. Therefore, developing flexible multifunctional sensing materials utilizing conductive polymers such as PANI and PPy is of great interest to researchers. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, electrospun CA fibers are often transformed into stable cellulose via deacetylation in NaOH/ethanol solution. 37,38 However, the deacetylation process is corrosive and time consuming, resulting in cumbersome operations and increased costs. 39 In this study, PAN is replaced by CA to the maximum extent without losing excessive flexibility of the hybrid fibers.…”
Section: Introductionmentioning
confidence: 99%